2022
DOI: 10.1002/env.2759
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal modeling of mature‐at‐length data using a sliding window approach

Abstract: Assessing maturity status of fish and invertebrate species is important for understanding population dynamics with results (e.g., estimates of reproductive potential) often used to inform fisheries management strategies (e.g., the setting of minimum legal size requirements for fishing). Maturity rates may vary substantially across a population's range, as well as between years. In addition, maturity data are typically obtained from fisheries-independent surveys that may be incomplete (or missing) from year to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As noted in our editorial for Part 1 of the special issue (Zammit‐Mangion et al 2023), environmental data analyses are often concerned with processes evolving in space and/or time, and therefore make extensive use of spatial or spatio‐temporal models. Most of the contributions to Part 2 of the special issue develop and apply such models: Yan, Cantoni, Field, Treble, and Mills Flemming (2023) consider a spatio‐temporal application in fisheries science that involves estimating the maturity of fish stock; Nie, Wang, and Cao (2023) apply functional data analysis to the problem of sub‐region estimation for daily bike‐share rentals; Laroche, Olteanu, and Rossi (2023) examine irregularly sampled left‐censored pesticide concentration data from France, developing new methodology for modeling spatio‐temporal heterogeneity; while Mukherjee, Bagozzi, and Chatterjee (2023) use spatio‐temporal fields to model climate and social instability interactions, as a framework for studying conflict. Several contributions also consider the problem of spatial/spatio‐temporal interpolation or emulation: Granville, Woolford, Dean, Boychuk, and McFayden (2023) tackle the problem of interpolating spatial data for generating a fire index for wildfires in Ontario, Canada, while Cartwright, Zammit‐Mangion, and Deutscher (2023) develop a spatio‐temporal emulator based on convolutional variational autoencoders.…”
Section: Application and Development Of Spatio‐temporal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted in our editorial for Part 1 of the special issue (Zammit‐Mangion et al 2023), environmental data analyses are often concerned with processes evolving in space and/or time, and therefore make extensive use of spatial or spatio‐temporal models. Most of the contributions to Part 2 of the special issue develop and apply such models: Yan, Cantoni, Field, Treble, and Mills Flemming (2023) consider a spatio‐temporal application in fisheries science that involves estimating the maturity of fish stock; Nie, Wang, and Cao (2023) apply functional data analysis to the problem of sub‐region estimation for daily bike‐share rentals; Laroche, Olteanu, and Rossi (2023) examine irregularly sampled left‐censored pesticide concentration data from France, developing new methodology for modeling spatio‐temporal heterogeneity; while Mukherjee, Bagozzi, and Chatterjee (2023) use spatio‐temporal fields to model climate and social instability interactions, as a framework for studying conflict. Several contributions also consider the problem of spatial/spatio‐temporal interpolation or emulation: Granville, Woolford, Dean, Boychuk, and McFayden (2023) tackle the problem of interpolating spatial data for generating a fire index for wildfires in Ontario, Canada, while Cartwright, Zammit‐Mangion, and Deutscher (2023) develop a spatio‐temporal emulator based on convolutional variational autoencoders.…”
Section: Application and Development Of Spatio‐temporal Modelsmentioning
confidence: 99%
“…Spatio‐temporal analyses often involve dealing with data which are recorded on differing time scales, spatial scales, or both. Jahid et al (2023) examine this problem in the context of animal tagging and abundance estimation for grizzly bears in Alberta, Canada; Yan et al (2023) consider aggregation for fisheries stocks in Atlantic Canada; and Laroche et al (2023) deal with aggregation when examining censored pesticide data. The more methodological side of this problem is considered by Roth et al (2023) for calibration methods of flood hazard projections, when integrating model outputs with differing resolutions.…”
Section: Sampling and Aggregationmentioning
confidence: 99%
“…Greenland halibut ( Reinhardtius hippoglossoides , Walhaum, 1792; also known as Greenland turbot or black halibut) is a large flatfish distributed primarily in arcto‐boreal cold and deep waters, with continuous populations along continental slopes of the North Pacific, Atlantic, and Arctic Oceans (Hedges et al, 2017; Vihtakari et al, 2021). The species exhibits strong sexual dimorphism with females growing larger (~120 cm vs. 70 cm), older (>30 years vs. >20 years; Treble et al, 2008), and maturing later (L/A50 61 cm/15 years vs. 44 cm/8 years; Morgan et al, 2003; Yan et al, 2022) than males (estimates from the Institute of Marine Research (IMR) database). Mark–recapture studies have shown that Greenland halibut can be a highly migratory species (Albert & Vollen, 2015; Boje, 2002; Vihtakari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%